Pengembangan Mamaca di Pamekasan Madura sebagai Penguatan Harmoni Kehidupan Sosial - Supadma Supadma; I Wayan Dana (Dance and Theatre Review, 2021)
The Development of Mamaca in Pamekasan Madura as Strengthening Harmony of Social Life. This study aims to develop one of the traditional performing arts, namely Mamaca in Pamekasan Regency, Madura Island, which is abandoned, especially by the local younger generation. Mamaca, which emphasizes the nobility of values and norms in its form and implementation, is capable of strengthening the nation’s character and the harmony of social life. Thus, this research is an effort to reconstruct local cultural and community values. Seeing its essential role, this research on Mamaca will be carried out in three years. Mamaca presents the values of local wisdom and uses the hermeneutic approach. The reinforcement is designed in the form of new Mamaca choreography according to the spirit of the times. It also reflects the will of the supporting community but still does not leave its primary source. The design of the form of presentation is based on an emic and ethical point of view, namely using a choreographic approach by involving the ideas of local artists or actors. The “new” Mamaca choreography was introduced to students of several elementary schools, as well as to existing performing arts groups. By introducing and teaching it to young children, it is hoped that the stronger and longer roots will be planted for growth. Its introduction and application are followed up by contesting it to motivate others in arts and to promote it to a broader audience, Mamaca can be developed outside its original area, but with similar traditional performing arts. Based on this plan, further development of choreography is also designed to be taught to children and adapted to their distribution area.Keywords: mamaca; Pamekasan Madura; local wisdom; national character;social harmony